A Review of Air Purification by Indoor and Outdoor Plants - Manju Madhavan; Abisha, AV; Leen Babu; Liyana K; Sanjana Chacko; Soniya A; Sheeja T Tharakan (Innovations in Biological Science Vol. 6, 2024)
This study focuses on the plants that improve the air quality and purify air. Air pollution can be reduced using phytoremediation by knowing the right plants to remove the pollutants. In the present study, the role of indoor and outdoor plants helps in air purification and compared the pollutants removed by selected indoor plants. The importance of the Air Pollution Tolerance Index (APTI) of selected outdoor plants was also analysed. Indoor air pollution, originating from various sources, accumulates and significantly impacts human health. Major pollutants like carbon monoxide, sourced from fuel and tobacco combustion, impair oxygen transport in the body, leading to headaches, fatigue, and reduced reflexes. The literature was retrieved through a search on electronic databases like Web of Science, Scopus, PubMed, and Google Scholar. The keywords and phrases used during the search were medicinal plants, mechanism of action, air pollution, indoor plants, and outdoor activity. Plants clean the air through the process of photosynthesis. Oxygenic photosynthesis involves the conversion of water and CO2 into complex organic molecules such as carbohydrates and oxygen.